PLATELET COUNT AND SPLEEN SIZE AS NON-INVASIVE PREDICTOR OF ESOPHAGEAL VARICES IN DECOMPENSATED CHRONIC LIVER DISEASE PATIENTS (The Research of Medical Science Review, 2025)
Objective: To determine the predictive value of non-invasive parameters (platelet count and spleen diameter) in determining esophageal varices in patients with Decompensated Chronic Liver Disease.Study design: Cross sectionalPlace & duration of study: The study will be carried out in the Department of Internal Medicine, Liaquat University of Medical and Health Sciences. Methodology: In this cross-sectional study, 335 age 18-70 years of both genders, with an established diagnosis of (any severity) decompensated chronic liver disease had duration of disease <6 months participated. Every recruited patient had a thorough medical history, Blood samples were taken from all participants for CBC (to look for platelet count), LFTS and ultrasound abdomen was carried out to look at spleen size. Data analysis were done using SPSS Version 26. The quantitative variables were presented as mean ±SD. Frequencies & percentages were calculated for qualitative variables. Contingency table (2 x 2) was made to calculate sensitivity, specificity, PPV, NPV and diagnostic accuracy of non-invasive parameters keeping endoscopy as gold standard. Results: The mean age of the patients was 57.82 + 10.22 years. Male female ratio was almost same. 167 (49.9%) were female and 168 (50.1%) were male. Most common indication was Ascites 226 (67.5%) and most common etiology of cirrhosis 142 (50.1%). the PPV, NPV, Sensitivity, specificity and diagnostic accuracy of platelet counts (a count of <150 platelets per microliter of blood) in predicting the esophageal varices in decompensated chronic liver disease patients was 74.5%, 75.1%, 67.8%, 68.3% and 71.3% respectively. Similarly, spleen size (more than 12 cm) had PPV, NPV, Sensitivity, specificity and diagnostic accuracy was 81.1%, 48.2%, 68.8%, 64.4% and 67.4% respectively. Conclusion: Our study concluded that the platelet count and spleen size are accurate noninvasive method of assessing EVs in our patients with decompensated liver cirrhosis